Infant weight trajectories and early childhood wheezing: the NINFEA birth cohort study. Issue 12 (1st July 2016) - Popovic, Maja; Pizzi, Costanza; Rusconi, Franca; Galassi, Claudia; Gagliardi, Luigi; De Marco, Laura; Migliore, Enrica; Merletti, Franco; Richiardi, Lorenzo
Abstract : Background: Rapid postnatal weight gain has been associated with wheezing and asthma in children, but it remains unclear whether it acts independently of overweight. We aimed to disentangle the roles of infant's size and weight gain velocity in the development of wheezing in early childhood using a novel method that allows for mutual adjustment for different aspects of growth. Methods: Data were obtained from the NINFEA questionnaires where weight measurements from birth up to 18 months of age were assessed in 4492 term singletons. Wheezing was defined as at least one episode of wheezing/whistling in the chest occurring between 6 and 18 months of age. The SuperImposition by Translation And Rotation model was used to estimate individual weight trajectories defined by three child-specific parameters: size, velocity and tempo, that is age at peak weight velocity. These parameters were standardised and related to wheezing using logistic regression with effects expressed as an increase of one SD. Results: A median of five weight measurements per child were obtained. Infant size (OR=1.28; 95% CI 1.12 to 1.46) and weight gain velocity (OR=1.30; 95% CI 1.15 to 1.48) were independently positively associated with wheezing. We found no evidence of an effect of tempo on infant wheezing. The estimates were changed only minimally after adjustment for potential confounders. Conclusions: Faster growth and larger size in the first 18 months of life are both independently associated with an increased risk of wheezing. These findings suggest that early growth patterns play a role in shaping the occurrence of wheezing.